Literature Review: Terapi Komplementer Untuk Mengurangi Mual Muntah Pada Masa Kehamilan - Ni Ketut Somoyani (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2020)
Nausea and vomiting during the first of pregnancy is one of the most common complaints from women. Nearly 50-90% of pregnant women experience nausea, vomiting in the early pregnacy. The purpose of this paper is to find out some evidence-based complementary therapies that can be done to reduce nausea and vomiting during pregnancy. The method used in this paper is to review the results of research related to complementary therapy in reducing nausea and vomiting during pregnancy. Based on the results of literature review on three journal articles, it can be explained that the intervention in the form of complementary therapy with peppermint aromatherapy is effective in reducing nausea and vomiting during pregnancy. From the results of the Pared Sample T-Test, the value of t = 11,000 and p = 0,000, where p 0.05, HI is accepted, means that there is an influence of pappermint aromatherapy to reduce vomiting in pregnant women.The administration of lemon aromatherapy (Citrus Lemon) can reduce nausea and vomiting during pregnancy, from 70% who experience moderate nausea and vomiting, down to 30% who experience moderate nausea and vomiting. For acupressure application at PC6 point, it shows that there is an effect of acupressure at PC 6 point on emisis gravidarum with p-value = 0,000. The results of this study can be used as reference material in providing non-pharmacological therapy to mothers who experience nausea and vomiting during pregnancy.